2003
DOI: 10.1074/jbc.m300945200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of the Melastatin-related Cation Channel TRPM3

Abstract: Proteins of the mammalian TRP (transient receptor potential) family form a heterogenous group of cation channels important for cellular Ca 2؉ signaling and homeostasis. Here we present the full-length sequence of TRPM3, a member of the melastatin-like subfamily (TRPM) of TRP channels. TRPM3 expression was found in human kidney and brain. HEK293 cells transiently transfected with TRPM3 showed a constitutive Ca 2؉ and Mn 2؉ entry. Whole-cell patch clamp experiments confirmed the spontaneous activity of TRPM3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
322
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(327 citation statements)
references
References 29 publications
(48 reference statements)
5
322
0
Order By: Relevance
“…miR-204 was detected in RNA from the choroid plexus, but not the cerebral cortex, whereas the neural-specific miR-124a was detected in the cortex and not the choroid plexus. miR-204 is located within the sixth intron of the transient receptor potential melastatin 3 (TRPM3) cation channel and is transcribed in the same direction as TRPM3 (Grimm et al, 2003;Lagos-Quintana et al, 2003;Rodriguez et al, 2004). TRPM3 is expressed in choroid plexus and eye (Oberwinkler et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-204 was detected in RNA from the choroid plexus, but not the cerebral cortex, whereas the neural-specific miR-124a was detected in the cortex and not the choroid plexus. miR-204 is located within the sixth intron of the transient receptor potential melastatin 3 (TRPM3) cation channel and is transcribed in the same direction as TRPM3 (Grimm et al, 2003;Lagos-Quintana et al, 2003;Rodriguez et al, 2004). TRPM3 is expressed in choroid plexus and eye (Oberwinkler et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The miR-204 miRNA is located in the intron of the TRPM3 gene, and TRPM3 is also expressed in the choroid plexus, suggesting that the miRNA and TRPM3 are derived from a single transcription unit in that tissue. TRPM3 encodes a cation channel, but its biological function is not known (Grimm et al, 2003;Oberwinkler et al, 2005). A subset of miRNAs is located within the introns of protein coding genes (Rodriguez et al, 2004), and analysis of microarray data has shown that the expression of several intronic miRNAs is correlated with the expression of the mRNA from the same locus (Baskerville and Bartel, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRPM2, TRPM3 and TRPM8 are Ca 2+ permeable nonselective cation channels, which differ substantially with respect to their activation stimuli (Chuang et al 2004;Grimm et al 2003;Hara et al 2002;Lee et al 2003;McKemy et al 2002;Peier et al 2002;Sano et al 2001;Wehage et al 2002). TRPM8 is activated by low temperature (Chuang et al 2004;Voets et al 2004a), while TRPM2 is stimulated by intracellular ADP-ribose, NAD + and oxidative stress (Hara et al 2002;Perraud et al 2001Perraud et al , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…TRPM8 is activated by low temperature (Chuang et al 2004;Voets et al 2004a), while TRPM2 is stimulated by intracellular ADP-ribose, NAD + and oxidative stress (Hara et al 2002;Perraud et al 2001Perraud et al , 2003). TRPM3 appears to be activated by hypoosmotic cell swelling, rises of intracellular Ca 2+ and by D-erythro-sphingosine (Grimm et al 2003(Grimm et al , 2004Lee et al 2003). Two other TRPM subfamily members, TRPM4 and TRPM5, are mainly permeable for monovalent cations, gated by increases in intracellular Ca 2+ and exhibit a pronounced voltage modulation (Hofmann et al 2003;Launay et al 2002;Liu and Liman, 2003;Nilius et al 2003;Prawitt et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To exclude that the individual proline substitutions led to channel inactivation, functional tests of the mutant channels were performed by using specific agonists. TRPV2 mutants were gated with diphenyl boronic anhydride (DPBA) (12), and TRPC6 mutants were gated with 1,2-didecanoyl-glycerol (DDG) (13,14) in calcium imaging experiments; TRPM2 mutant gating was tested in patch-clamp experiments using ADP-ribose (15, 16) (SI Fig. 8 C-E).…”
Section: Tm5 Susceptibility Is a General Feature Of Trpmls As Well Asmentioning
confidence: 99%